Life-course socioeconomic differences and social mobility in preventable and non-preventable mortality: a study of Swedish twins. (30th March 2019) - Ericsson, Malin; Pedersen, Nancy L; Johansson, Anna L V; Fors, Stefan; Dahl Aslan, Anna K
Abstract: Background: Despite advances in life expectancy, low socioeconomic status is associated with a shorter lifespan. This study was conducted to investigate socioeconomic differences in mortality by comparing preventable with non-preventable causes of death in 39 506 participants from the Swedish Twin Registry born before 1935. Methods: Childhood social class, own education, own social class and social mobility were used as separate indicators of socioeconomic status. These data were linked to the Swedish Cause of Death Register. Cause of death was categorized as preventable or non-preventable mortality according to indicators presented in the Avoidable Mortality in the European Union (AMIEHS) atlas. Using Cox proportional hazard models, we tested the association between the socioeconomic measures and all-cause mortality, preventable mortality and non-preventable mortality. Additional co-twin control analyses indicated whether the associations reflected genetic confounding. Results: The social gradient for mortality was most prominent for the adult socioeconomic measures. There was a social gradient in both preventable mortality and non-preventable mortality, but with an indication of a moderately stronger effect in preventable causes of death. In analyses of social mobility, those who experienced life-time low socioeconomic status (SES) or downward social mobility had an increased mortality risk compared with those with life-time high SES and upward social mobility. Adjustments for genetic confounding did not change the observed associations for education, social class or social mobility and mortality. In the co-twin control analyses of reared-apart twins, the association between childhood social class and mortality weakened, indicating possible genetic influences on this association. Conclusions: Our results indicate that there is an association between low adult socioeconomic status and increased mortality independent of genetic endowment. Thus, we do not find support for indirect social selection as the basis for mortality inequalities in Sweden